Computation in Linguistics A Case Book - Spolsky, Bernard; Garvin, Paul L. (Indiana University Press, 1967)
Making a valuable contribution to a rapidly growing phase of linguistic science, the editors bring together enlightening case studies which demonstrate the varied use of computation and computers in the solution of problems in linguistis. Computational approaches to specific problems in formal languages, data processing, comparative linguistics, automatic parsing and translation, automatic verification procedures, and automated instruction are thoroughly analyzed. Contributors include Paul L. Garvin, R Banerji, W. C. Crossgrove, Roger Shuy, Volney Steffire, Alber Schütz, D. L. Stampe, S. N. Jacobson, Dan M. Matson, Fred C. Peng, Paul D. Samuelsdorff, Richard L. Venezky, Oswald Werner, Mary Lou Joynes, and Bernard Spolsky.